The Effect of Health Education using Audiovisual Towards Knowledge about Brushing Teeth Correctly on Students - Dewi Woro; Radella Hervidea; Tyas Deswita Ningrum (Indonesian Journal of Global Health Research, 2022)
Oral and dental health is the most common health problem in Indonesian society. At the Sritejokencono Puskesmas in 2019, there were 1049 oral health problems and were included in the top 10 diseases there. There are still many dental and oral health problems due to the lack of optimal school dental health (UKGS) activities carried out by the puskesmas, one of which is health education activities. This study used a quantitative type of research with a pre-experimental character and a research This study uses a quantitative research with a pre-experimental nature and a research design using a one-group pretest – posttest design. The population in this study were all 3rd grade students at SD N 1 Sritejokencono Central Lampung totaling 40 students with 34 students. This research was conducted on 2 and 3 August 2020 at SDN 1 Sritejokencono, Central Lampung. data collection by, before respondents were given health education through video, respondents first did a pre-test then respondents were given health education by playing a video brushing their teeth correctly for 5 minutes, then respondents filled out questionnaires or post-test sheets, then carried out. After the normality test, the results of the data are not normally distributed, then the Wilcoxon test is used.The results showed that there was an effect of health education using audiovisual on the knowledge of correct tooth brushing in grade 3 students at SD N 1 Sritejokencono, Central Lampung in 2020 with a p value of 0.000 (p value <α = 0.05).